Viral (per)versions of power in Paolo Sorrentino's diptych Loro. Issue 3 (August 2020) - Mariani, Annachiara
Abstract : This article examines Paolo Sorrentino's portrayal of moral degradation and pursuit of power in his twin biopics about Silvio Berlusconi: Loro 1 and Loro 2 (2018). It does so by performing a psychological reading of Sorrentino's representation of Berlusconi, as someone suffering from a personality disorder characterised by excessive power striving. It argues that this obsession with power also affects most of the films' characters, who become obsessed with entering Berlusconi's inner circle – the pinnacle of wealth and power in a neoliberal society. In particular, it argues that their power striving circulates 'virally' in the film's narrative; the characters are willing to do anything to befriend their idol and attain absolute power. The ensuing analysis shows that Sorrentino's portrayal of Berlusconi – as the embodiment of a highly dysfunctional and obsessive, viral quest for power – comes to represent the deep pervasiveness of corruption, hedonism and commodification that marked the Second Republic.